2009
DOI: 10.1109/tgrs.2008.2002076
|View full text |Cite
|
Sign up to set email alerts
|

Fire Information for Resource Management System: Archiving and Distributing MODIS Active Fire Data

Abstract: Technological advances have driven all aspects of Earth observation data, including improvements realized in sensor characteristics and capabilities, global data processing, near realtime monitoring, value-added products, and the distribution of global products. In particular, the growth of the World Wide Web is contributing to an increase in the global user base. The synergy of remote sensing, geographic information systems (GIS), Internet, and mobile phone technologies is revolutionizing the way in which sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
150
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(165 citation statements)
references
References 27 publications
2
150
0
1
Order By: Relevance
“…We analyzed peat fire occurrence in Borneo based on a fire hotspot database, spanning from January 1, 1997, to August 31, 2009, (21). As there is not a single sensor system which covers the full time period, a separate analysis for 2 investigation periods was carried out: (a) from 1997 to 2000 using fire hotspots from the Advanced Very High Resolution Radiometer (AVHRR) on board the National Oceanic and Atmospheric Administration (NOAA) satellite and from the Along-Track Scanning Radiometer (ATSR) on board the European Remote Sensing Satellite 2 (ERS-2), and (b) and from 2001 to 2009 using fire hotspots from the MODerate resolution Imaging Spectroradiometer (MODIS) on board the Terra and Aqua satellites (21,22). This fire hotspot time series showed that the peat fires in 2006 were the most severe after the well known 1997-1998 fire disaster.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed peat fire occurrence in Borneo based on a fire hotspot database, spanning from January 1, 1997, to August 31, 2009, (21). As there is not a single sensor system which covers the full time period, a separate analysis for 2 investigation periods was carried out: (a) from 1997 to 2000 using fire hotspots from the Advanced Very High Resolution Radiometer (AVHRR) on board the National Oceanic and Atmospheric Administration (NOAA) satellite and from the Along-Track Scanning Radiometer (ATSR) on board the European Remote Sensing Satellite 2 (ERS-2), and (b) and from 2001 to 2009 using fire hotspots from the MODerate resolution Imaging Spectroradiometer (MODIS) on board the Terra and Aqua satellites (21,22). This fire hotspot time series showed that the peat fires in 2006 were the most severe after the well known 1997-1998 fire disaster.…”
Section: Resultsmentioning
confidence: 99%
“…22; http://maps.geog.umd.edu/firms/) to estimate the burned peat area for Indonesia. Previous studies showed that there is a reasonable correlation between burned areas deduced from MODIS hotspots and those derived from high resolution Landsat imagery, especially in peatlands, although a fire may cover the whole area of the sensor element (1 square km) or only a small fraction of it (12,21,32).…”
Section: Methodsmentioning
confidence: 99%
“…Short duration fires might be also missed if not at overpass time. Thus, AF products are inadequate if total burned area is wished to derive (Pereira et al 2003), but are superior in rapid mapping applications (Davies et al 2009). They are also a valuable alternative in estimating consumed biomass and its emissions directly from FRP (e.g.…”
Section: Frequência Sazonalidade E Intensidade De Incêndio Na Regiãomentioning
confidence: 99%
“…In the World Bank's disaster management portfolio, only projects addressing floods and droughts have been more numerous (IEG 2006 (Calle and Casanova 2008). Among the projects contributing to this program is the Fire Information for Resource Management System (FIRMS), a set of applications providing access to near real-time web-based fire maps and associated data sets without exceeding the limited download capacities of many developing countries (Davies et al 2009). While close interaction with focus groups of Earth observation data users in Central America, Africa, and Asia was important to the design of these applications, the project is provider-initiated and interaction with users have revolved around the processing and dissemination of satellite data, not data acquisition.…”
Section: Assistancementioning
confidence: 99%